Diagnostic pitfall in a large cell lung cancer with testicular metastasis synchronous malignant pleural mesothelioma patient: A case report. Issue 15 (15th June 2022) - Jiang, Lisha; De Souza, Veylenta A.; George, Nithin M.; Rai, Nitya P.; Shi, Ming; Che, Guowei
Abstract: Large cell lung cancer metastases to the testis are scarce, although it is the most common malignancy and the most common site of metastases for breast, colorectal and kidney cancers. We hereby report a 28‐year‐old male patient admitted to our hospital with a chief complaint of scrotal enlargement, accompanied by chest pain and progressive dyspnea. The definite diagnosis was malignant pleural mesothelioma with the synchronous occurrence of large cell lung cancer with testicular metastasis. Sophisticated clinical manifestation of symptoms led to a time‐consuming diagnosis, while the patient's condition deteriorated rapidly. Herein, we present this case to share our hard‐learnt experience to increase clinician awareness and contribute to the information in the literature. Abstract : Testicular metastasis as initial manifestation of large cell lung cancer with the synchronous occurrence of malignant pleural mesothelioma, bilateral hydrothorax were increasing, patient's performance kept deteriorating, the diagnosis and treatment were in a dilemma.